Time to onset of improvements in Quality of Life from Temperature-controlled Laminar Airflow (TLA) in severe allergic asthma. (February 2019) - Bjermer, L.; Eriksson, G.; Radner, F.; Peterson, Stefan; Warner, J.O.
Abstract: Background: Allergen avoidance is important in allergic asthma management. Nocturnal treatment with Temperature-controlled Laminar Airflow (TLA; Airsonett ® ) has been shown to provide significant reduction of exposure to allergens in the breathing zone, leading to long-term reduction in airway inflammation and improvement in quality of life. Allergic asthma patients uncontrolled on GINA step 4 were found to benefit the most. A frequently asked question from clinicians and funders is related to time to onset (TTO) of improvements for patients using TLA. Methods: Asthma Quality of Life Questionnaire (AQLQ) scores were collected in a previous study. TTO of improvements in Quality of Life was analysed for difference (TLA-placebo) in Area-under-Curve using backwards deletion from 12, 9, 6, 3 down to 1 month for the AQLQ total score, the four individual domains and specifically the sleep question. Results: Patients with uncontrolled asthma on GINA step 4 (n = 87)) reported a statistically significant and clinically relevant (≥0.5 point) improvement in total AQLQ score (0.57; p = 0.009) after 3 months treatment for TLA over placebo. The shortest TTO was within 1 month for the environmental domain (0.68; p = 0.016) and the sleep question (0.771; p = 0.037). TTO for the emotional and symptom domains was 3 months (0.66; p = 0.020 and 0.64; p = 0.014 respectively) and for the activity domain 6 months (0.47; p = 0.036). Conclusion: Nocturnal avoidance of allergens using TLA provided a statistically significant and clinically relevant improvement in total AQLQ score within 3 months in patients in the GINA 4 + ACT<18 group. Questions related to sleep quality may provide the first signal of response already within a month after commencing treatment. Highlights: Nocturnal avoidance of allergens are important for treating asthma. Temperature Laminar Airflow (TLA) is effective in symptomatic severe asthma. Onset of the effects of TLA occurs within 3 months for Asthma Quality of Life. Sleep-related TLA-effect may be the earliest marker of effects (within one month). Onset of effects helps treating physicians evaluating effects of individual patient.